Optimizing the Role of Teachers as Facilitators in the Use of Technology-Based Learning Media in Elementary Schools - Jufri; La Ode Fajrul Islam Sabti (AIQU: Journal Multidiscipliner of Science, 2024)
The application of technology in learning in elementary schools must also be balanced with good supervision so that the use of the media runs optimally. Teachers need to ensure that students use technology correctly and do not misuse it. The purpose of this study is to determine the optimization of the role of teachers as facilitators in the use of technology-based learning media at Elementary School 2 Kaobula. This study is qualitative descriptive, based on the results of field research and uses a field research methodology. Semantic approach research is a type of research. In the use of technology-based learning media through semantic methods, so that the competence and talent of researchers to reveal a subjective event and choose informants in accordance with applicable provisions and requirements determine the source of data for research, so that the data needed by researchers is truly in accordance with the nature or facts that exist. The results of this study indicate that the use of technology-based learning media at Elementary School 2 Kaobula has had a significant positive impact on the learning process. With the role of teachers as effective facilitators, the use of technology can create an innovative and interesting learning atmosphere, as well as increase student involvement and motivation.